Development of an integrated pointing device driver for the disabled. - Shih C (Disability & Rehabilitation: Assistive Technology, 2010)
Purpose. To help people with disabilities such as those with spinal cord injury (SCI) to effectively utilise commercial pointing devices to operate computers. This study proposes a novel method to integrate the functions of commercial pointing devices. Method. Utilising software technology to develop an integrated pointing device driver (IPDD) for a computer operating system. Results. The proposed IPDD has the following benefits: (1) it does not require additional hardware cost or circuit preservations, (2) it supports all standard interfaces of commercial pointing devices, including PS/2, USB and wireless interfaces and (3) it can integrate any number of devices. The IPDD can be selected and combined according to their physical restriction. Conclusions. The IPDD is a novel method of integrating commercial pointing devices. Through IPDD, people with disabilities can choose a suitable combination of commercial pointing devices to achieve full cursor control and optimise operational performance. In contrast with previous studies, the software-based solution does not require additional hardware or circuit preservations, and it can support unlimited devices. In summary, the IPDD has the benefits of flexibility, low cost and high-device compatibility.